Contribution of Revised International Prognostic Scoring System Cytogenetics to Predict Outcome After Allogeneic Stem Cell Transplantation for Myelodysplastic Syndromes. Issue 8 (August 2015) - Gauthier, Jordan; Damaj, Gandhi; Langlois, Carole; Robin, Marie; Michallet, Mauricette; Chevallier, Patrice; Beguin, Yves; N'guyen, Stéphanie; Bories, Pierre; Blaise, Didier; Cornillon, Jérôme; Clavert, Aline; et al.
<x xml:space="preserve">Abstract</x> Background The prognosis of myelodysplastic syndromes (MDS) after allogeneic stem cell transplantation is critically determined by cytogenetic abnormalities, as previously defined by International Prognostic Scoring System (IPSS) cytogenetics. It has been shown that a new cytogenetic classification, included in the IPSS-R (cytogenetic-IPSS-R [C-IPSS-R]), can better predict the outcome of untreated MDS patients. Methods In this study, we assessed the impact of the IPSS-R cytogenetic score (C-IPSS-R) on the outcome of 367 MDS patients transplanted from HLA-identical siblings or HLA allele-matched unrelated donors. Results According to the C-IPSS-R, 178 patients (48%) fell in the good risk, 102 (28%) in the intermediate risk, 77 (21%) in the poor risk, and 10 (3%) in the very poor risk group. In multivariate analysis, after a median follow-up of 4 years, the poor and very poor-risk categories correlated with shorter overall survival (OS) (4-year OS, 32%; hazard ratio [HR], 1.59; P = 0.009 and OS, 10%; HR, 3.18; P = 0.002, respectively) and higher cumulative incidence of relapse (CIR) (CIR, 52%; HR, 1.82; P = 0.004 and CIR, 60%; HR, 2.44; P = 0.060, respectively). Conclusions Overall, the C-IPSS-R changed the IPSS cytogenetic risk only in 8% of cases but identified a new risk group, the very poor C-IPSS-R category, with dismal outcome after allogeneic stem cell transplantation (10% 4-year OS, 60% 4-year CIR). Posttransplantation maintenance therapy should be investigated in prospective trials for patients with high-risk C-IPSS-R karyotypes.